Laser treated super hydrophobic glass for solar PV self cleaning application: a SWOT-TWOS-based analysis - Rahool Rai; Mahadzir Ishak; Sudhakar Kumarasamy; Aiman Bin Mohd Halil; M M Quazi (Materials Research Express)
With the increasing demand for sustainable energy solutions, laser surface modification has emerged as a promising technique to enhance the functional properties of materials, particularly in optimizing glass surfaces for solar applications that require hydrophobicity and environmental resilience to improve photovoltaic performance and durability. Consequently, a SWOT-TWOS analysis is conducted to identify the strengths, weaknesses, opportunities, and threats of integrating these technologies. This analysis assesses the advantages, such as improved light diffusion and reduced glare, along with the disadvantages, including decreased transparency and potential glass damage. Additionally, there are opportunities for technological and sustainable advancements, as well as threats such as quality control issues. The SWOT analysis for Laser Treated Super Hydrophobic Glass in solar PV self-cleaning applications revealed a distribution of 42% technical, 26% environmental, and 21% economic factors, with 11% of factors spanning all three domains. Notably, the two elements are complex and interdependent across multiple domains, underscoring the intricate influences affecting the viability of this technology. By identifying these characteristics, the study aims to provide a comprehensive understanding of laser texturing potential and limitations, as well as recommendations for future research and practical applications.